Brief Report: Tubulointerstitial Damage in Lupus Nephritis: A Comparison of the Factors Associated With Tubulointerstitial Inflammation and Renal Scarring. Issue 11 (24th September 2018) - Londoño Jimenez, Alejandra; Mowrey, Wenzhu B.; Putterman, Chaim; Buyon, Jill; Goilav, Beatrice; Broder, Anna
Abstract : Objective: To characterize and compare the factors associated with tubulointerstitial inflammation (TII) and tubulointerstitial scarring, defined as interstitial fibrosis and/or tubular atrophy (IF/TA), in patients with lupus nephritis (LN). Methods: We identified systemic lupus erythematosus patients who had renal biopsy results consistent with LN between 2005 and 2017. Clinical data were collected from medical records. Multivariable logistic regression models were fitted to assess factors associated with TII and with IF/TA (moderate‐to‐severe versus none/mild). Results: Of 203 LN patients included, 41 (20%) had moderate‐to‐severe TII, 45 (22%) had moderate‐to‐severe IF/TA, and 21 (10%) had both. Multivariable logistic regression models showed that moderate‐to‐severe TII was associated with a shorter disease duration, African American race, proliferative LN, and an estimated glomerular filtration rate (eGFR) of <60 ml/minute/1.73 m 2 at the time of biopsy. Hydroxychloroquine use was associated with significantly lower odds of moderate‐to‐severe TII (odds ratio 0.27 [95% confidence interval 0.10–0.70], P = 0.008). Similar to TII, factors associated with moderate‐to‐severe IF/TA included proliferative LN and eGFR <60 ml/minute/1.73 m 2 at the time of biopsy. In addition, the presence of moderate‐to‐severe TII and older age was associated with moderate‐to‐severe IF/TA. None of the routinely available serologic markers—including anti–double‐stranded DNA antibodies, anti‐Ro/La antibodies, and low complement—were associated with tubulointerstitial damage. Conclusion: The use of hydroxychloroquine was strongly associated with less inflammation, while the presence of TII, proliferative LN, and low eGFR were major determinants of tubulointerstitial scarring. Identifying modifiable factors is critical for the development of better preventive and therapeutic strategies with the goal of improving survival in patients with lupus‐related kidney disease.